FEA of SFRC three ribbed wall panel / Azrul Md Din - Md Din, Azrul (2014)
This finite element study was carried out to investigate the steel fibre reinforced concrete with three (3) ribbed wall (SFRC-3RW) panel containing reinforced wire mesh (BRC) subjected to axial and eccentric loading also its load bearing response behavior. A ribbed wall with steel reinforced was modeled with finite element analysis software LUSAS 14.7 using three dimensional modeling and non-linear finite element analysis. The SFRC-3RW panel was subjected to axial and eccentric loading to observe and investigate its buckling effect, the load bearing response behavior and compare with SFRC Plain Wall (PW). The SFRC-3RW and PW was using concrete grade 30 with 0.5% steel fibre content. The SFRC-3RW ultimate load bearing is 581 kN with maximum compression vertical and lateral displacement by 2.36 mm and 6.16 mm respectively compared to SFRC-PW with eccentric loading (SFRC-PWe) is 577 kN with maximum compression vertical and lateral displacement by 2.31 mm and 8.24 mm. The reduction in concrete volume and ultimate load capacity were 20% and 0.33% from SFRC-PWe which SFRC-3RW save the concrete amount and given higher load capacity compared to SFRCPWe. It can be concluded that the load bearing capacity for SFRC-3RW with BRC is acceptable and can withstand vertical pressure also reducing the amount of concrete usage.